Perceived Stress and Burden of Care in Elderly Caregivers: The Moderating Role of Resilience - Mahsa Jafari; Fardin Alipour; Ghoncheh Raheb; Mostafa Mardani (University of Social Welfare & Rehabilitation Sciences, 2022)
Objectives This study aimed to investigate the moderating role of resilience in the association between perceived stress and the burden of care among elderly caregivers at nursing homes in Tehran in 2016. Methods & Materials In this cross-sectional, correlational study, the data were collected from 142 caregivers engaged in nursing homes in Tehran, of which 50 were men and 92 were women, through the census sampling method. Research tools included the questionnaire of perceived stress-14 (PSS-14), Cohen et al., (1983), Zarit et al. (1986) Burden of care questionnaire, and connor and davidson resilience questionnaire (2003). The collected data were analyzed in SPSS software v. 20. The significance level was set at P<0.05. Results The results showed that the average perceived stress score (35.11) was higher than the average (28). The burden of care was significantly positively associated with perceived stress (r>0 or P=0.001), and there was a negative and significant relationship between resilience and responsibility of care (β=0.110). Also, the interaction effect of perceived stress and resilience on the burden of care was negative and significant, and resilience moderated the relationship between perceived stress and care burden (P<0.001). Conclusion According to a positive relationship between perceived stress and burden of care among elderly caregivers and the moderating effect of resilience on this relationship, governmental and non-governmental organizations in the elderly field and health policymakers should bring in the concept of resilience in their executive actions, policies, and protocols and improve it through proper training interventions. Further research is needed to study other internal and external moderating factors to improve the service quality and address the psychological, social, and physical complications of elderly caregivers.